Reformulating Water Policy: Reaffirming Farmers’ Rights and Developing Climate-Adaptive Governance Post-Constitutional Court Decision - Hari Kusuma Yuda Tama; Waluyo Waluyo (International Journal of Law, Crime and Justice, 2025)
ada